Environmental efficiency and its determinants in the development of China's western regions in 2000–2014. Issue 2 (3rd April 2017) - Yin, Chuanbin
ABSTRACT: In this study, we measure the environmental efficiency of western China in 2000–2014 by the super-efficiency slacks-based measure model which considers the undesirable outputs. The results show that the environmental efficiency of western China is low and rank behind in the national level. The environmental efficiency is lower than the traditional efficiency which reflects that the economic growth in 2000–2014 has paid high environmental costs. The difference between the traditional efficiency and environmental efficiency experienced "inverted U"-type trend change. The environmental efficiency of the western provinces presented differentiated developing trend and the differences between the western provinces were enlarging. The environmental efficiency of the western regions was not only lower than that in the eastern regions with a big gap but also lower than that in the central regions. Through the convergence test, we found that the environmental efficiency gap between the western and the eastern regions was gradually expanding; meanwhile, the environmental efficiency gap between the central and the western regions was narrowing. This paper also analyzes the determinants of environmental efficiency by the tobit model and then addresses.